The Effectiveness Of The Farmer Card In Muaradua Kec, South Oku District - Ruslain Ruslain; Munajat Munajat; E. Yunita Sari (PT. Anagata Sembagi Education, 2024)
Fertilizer is one of the most important means of production as an effort to provide sector support so that production yields can increase. This effort is done by providing subsidized fertilizer based on the definitive plan of group needs (RDKK). RDKK is the basis for the distribution of subsidized fertilizers to distributors that can be obtained through farmer cards. The farmer card program aims to ensure that subsidized fertilizer is distributed to those who are entitled to it. The target of subsidized fertilizer recipients is based on several principles, including the right type, right amount, right quality, right location, right time, and right price. This research will be conducted in Muaradua Sub-district, South OKU District, using the survey method as the research approach. Determination of the number of samples will use the Slovin Formula approach which is obtained by 76 farmers who use farmer cards. In order to answer the objectives of this study, a Likert scale was used to measure the effectiveness of the 6 precise indicators. The results obtained show that the right time, quality and quantity are not effective while the accuracy of price, type and place are effective.